Refiguração do tempo histórico pela ficção - José Antonio Segatto; Maria Célia Leonel (Estudos de Literatura Brasileira Contemporânea)
M. Bakhtin claims that the representation of events, relations and processes by the novel must embrace the totality of an epoch-it must present a peculiar space and temporal concatenation, which is expressed literarily. This idea contain the main elements to understand and analyze of the novel Leite derramado by Chico Buarque, published in 2009, which is the object of this study. The narrative figures at least two main epochs of the Brazilian history: the first starts in the 19th century and reaches the 1930s, the other starts at this time and reaches the beginning of the 21st century. It represents the historical saga of the decadence of a social category (a part of the dominant class), personified by the family Assumpção, its ethical and cultural values, its world conceptions and its behavior. The narrative also stylizes the social and moral dissolution of this family and puts many problems-from human and existential problems to historical and political ones – to be pondered by the reader.